Sero-Prevalence of Hepatitis B and Hepatitis C and the Impact of Their Co-Infection with Hiv on Immunologic Parameters on Hiv Infected Adults from Kisumu West Sub-County ,Kisumu County. - Ouma., Jew, O. (JOOUST, 2020)
Viral hepatitis and Human Immuno-deficiency Virus (HIV) infections are significant causes of morbidity and mortality all over the world, more especially in underdeveloped countries. Co-infections with HIV and Hepatitis B Virus (HBV) or HIV and Hepatitis C Virus (HCV) present significant challenges to infected individuals, health care providers and investment in medical care. Hepatitis infections present with different prevalence rates in different parts of the world, affecting c • approximately 10% of persons with HIV. However, there is a paucity of data regarding prevalence of the hepatitis B and hepatitis C in HIV infected individuals from Kisumu West Sub-County, despite high prevalence of HIV. Therefore, the objective of this study was to determine sero-prevalence of viral hepatitis in HIV infected adults from Kisumu West Sub-County. Specifically, this study evaluated gender disparity in prevalence of HIV positive adults with and without HBV and HCV; the age disparity in prevalence of HIV positive adults with and without HBV and HCV; the Cluster of Differentiation 4 (CD4) clinical characteristics of the co¬-infections and Alanine Amino Transferase (ALT) clinical characteristics of the co--infections. A sample size of 492 HIV positive adults above 18 years of age was used in the study. The data was analyzed using SPSS Version 20.0 and Graph pad prism VS software’s. The prevalence of hepatitis diseases in HIV positive subjects was 5.89% for Hepatitis B, and 2.85% for Hepatitis C. The HBV positivity was most prevalent in age group' 3 8-4 7 years while HCV positivity was most prevalent in the age bracket of 28• 3 7 years. This study suggests that there is no statistical association between the age groups and the hepatitis B and C infections (p=0.454 and 0.589 respectively). However, Hepatitis B positivity was higher in males than in females (p=0. 0215). Significantly higher CD4 mean values were observed in females compared to males (p=0.0019) while females had significantly lower ALT values compared to males (p=0.004). The mean value of CD4 in Hepatitis positive participants was non-significantly lower compared to CD4 cells in Hepatitis negative participants. Higher non-statistically significant mean values for ALT were observed in Hepatitis C positive compared to Hepatitis C negative participants. Being of public health importance, knowing the prevalence of these 2 diseases especially in the HIV infected group still becomes important for public health intervention strategies. A similar study that would encompass more variables for example educational status of study participants, risk factors that relate to the Hepatitis B and C diseases in the HIV positive participants and economic system of the study participants
Keywords: Sero-Prevalence.; Hepatitis B and Hepatitis C.; Co-Infection with Hiv.; Immunologic Parameters.; Hiv Infected Adults.; Kisumu West.